2020
DOI: 10.1002/jlb.1mr0720-185rr
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitinase in B cell development and function

Abstract: Ubiquitinases are a select group of enzymes that modify target proteins through ubiquitination, which plays a crucial role in the regulation of protein degradation, location, and function. B lymphocytes that originated from bone marrow hematopoietic stem cells (HSC), exert humoral immune functions by differentiating into plasma cells and producing antibodies. Previous studies have shown that ubiquitination is involved in the regulation of the cell cycle and signal transduction important for B lymphocyte develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Furthermore, by analysing the DEGs of immune cells in SMGs and PBMCs of patients with IgG4-RD, we found that UBC , TOMM7 , RACK1 , NACA and UBA52 were the shared genes (figure 5H). UBC and UBA52 are ubiquitination-related genes and protein ubiquitination plays a crucial role in T-cell and B-cell development and function processes 20 21…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by analysing the DEGs of immune cells in SMGs and PBMCs of patients with IgG4-RD, we found that UBC , TOMM7 , RACK1 , NACA and UBA52 were the shared genes (figure 5H). UBC and UBA52 are ubiquitination-related genes and protein ubiquitination plays a crucial role in T-cell and B-cell development and function processes 20 21…”
Section: Resultsmentioning
confidence: 99%
“…E3 Ub ligase Hrd1 mediates the downregulation of pre‐BCR through ubiquitination and promotes the maturation of pre‐B cells. 878 …”
Section: Ubiquitinationmentioning
confidence: 99%
“…E3 Ub ligase Hrd1 mediates the downregulation of pre-BCR through ubiquitination and promotes the maturation of pre-B cells. 878 Viruses can escape from immunity by degrading target proteins. For example, the CoV nucleocapsid (N) protein of SADS-CoV interacts with RIG-I and promotes its K27-, K48-, and K63-linked ubiquitination to induce RIG-I degradation, which further inhibits the host IFNβ response.…”
Section: Ubiquitination In Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitination and deubiquitination are also important processes in the regulation of B cell activation, proliferation, and apoptosis during development and their functional diversification and activation in innate and humoral immune responses 25 . A systems-wide analysis of B cell receptor signalosomes has identified USP8 as an interacting component upon stimulation 26 .…”
Section: Introductionmentioning
confidence: 99%